The Effect Of Auditor Knowledge, Work Experience On Audit Judgment With Task Complexity As A Moderating Variable - Rassel Rassel; Siti Jubaedah (Journal of Accounting and Auditing, 2025)
Purpose–This study aims to analyze the effect of auditor knowledge and work experience on audit judgment with task complexity as a moderating variable. This study highlights the importance of professional knowledge, work experience, and understanding of task complexity in supporting more accurate audit decision making. Design/methodology/approach–This study uses a quantitative method with a correlational approach. Data were collected through questionnaires distributed to auditors who are members of the Public Accounting Firm (KAP). Sampling was done by snowball sampling method, resulting in a total of 30 respondents. Data analysis was carried out using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. Findings–The results showed that auditor knowledge and work experience have a positive and significant effect on audit judgment. However, task complexity was found not to moderate the relationship between auditor knowledge and work experience on audit judgment. This shows that the level of auditor knowledge and experience has a significant direct contribution in producing quality audit decisions, regardless of the level of task complexity faced. Research limitations/implications–This study uses data obtained from questionnaires, so the results depend on the perceptions of respondents. In addition, the scope of respondents is limited to auditors who are members of KAP, so generalization of the results needs to be done carefully.